Hermeneutika Hudud menurut Muhammad Syahrur: Telaah tentang Relevansi Pemakaian Jilbab dengan Perkembangan Zaman - Irfansyah Irfansyah; Khairunnisa Khairunnisa (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2023)
The interpretation of clothing, if understood using a classical approach, would result in stagnant interpretations that are irrelevant to the essence of the Qur'an, which should be related to the development of time and also enter the world of fashion. Thus, Muhammad Syahrur offers a new approach to interpreting the Qur'an, namely the hermeneutics of hudud theory. This research reinterprets the meaning of the Jilbab by using the hermeneutics of hudud theory as an analytical tool. This study falls under the category of library research, and data collection is done through descriptive-qualitative literature review. The main references for this writing include the works of Muhammad Syahrur and other related literature as supporting sources. The research findings indicate that Syahrur interprets the word